Factors Influencing Patient Satisfaction In The Inpatient Installation of Manado City Regional General Hospital - Vidi Veronika Waroka; Grace Esther Caroline Korompis; Harsali Fransiscus Lampus (International Journal of Science and Environment (IJSE), 2026)
Background: Patient satisfaction is a key indicator for evaluating the quality of healthcare services, particularly in inpatient care. It is influenced by both the quality of interactions with healthcare personnel and the condition of hospital facilities. Hospitals are therefore expected to continuously improve service delivery to meet patients' expectations and needs. ObjectiveThis study aims to identify the factors influencing patient satisfaction in the Inpatient Installation of Manado City Regional General Hospital.Methods: A quantitative research method with a cross-sectional design was employed. The study population included patients who received inpatient care at Manado City Regional General Hospital from January to August 2025. With an average of 134 inpatients per month, a sample of 100 respondents was determined using the Lemeshow formula. Data collection utilized a validated and reliable questionnaire. Analysis consisted of univariate statistics, chi-square tests for bivariate analysis, and logistic regression for multivariateanalysis. Results:The study found significant relationships between patient satisfaction and the following service quality dimensions: tangible (p = 0.000), responsiveness (p = 0.001), assurance (p = 0.006), reliability (p = 0.015), and empathy (p = 0.017). Among these, tangible (physical evidence) was identified as the most dominant factor influencing satisfaction.Conclusion: All five dimensions—tangible, reliability, responsiveness, empathy, and assurance—significantly influenced patient satisfaction. However, the tangible aspect (physical facilities, cleanliness, and appearance of staff and infrastructure) was the most influential factor. These findings suggest that Manado City Regional General Hospital should prioritize improvements in physical infrastructure, facility maintenance, cleanliness, and the readiness of medical equipment to enhance patient satisfaction.